2002
DOI: 10.1074/jbc.m108226200
|View full text |Cite
|
Sign up to set email alerts
|

Partly Ordered Synthesis and Degradation of Glycogen in Cultured Rat Myotubes

Abstract: The following questions concerning glycogen synthesis and degradation were examined in cultured rat myotubes. 1) Is synthesis and degradation of the individual glycogen molecule a strictly ordered process, with the last glucosyl unit incorporated into the molecule being the first to be released (the last-in-first-out principle), or is it a random process? 2) Are all glycogen molecules in skeletal muscle synthesized and degraded in phase (simultaneous order) or out of phase (sequential order)? Basal glycogen st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 22 publications
7
41
0
Order By: Relevance
“…Using biochemical measurements of PG and MG in human skeletal muscle, we have shown that PG accumulation is the initial event during glycogen resynthesis (0 -4 h) followed by increases in MG (4 -24 h) (2). These data are consistent with the findings of Elsner et al (11), who have demonstrated using radiolabeled glucose a doubling of glycogen concentration in the early phases of glycogen resynthesis yet no increase in glycogen granule size in cultured rat myotubes. These findings have also been confirmed visually using transmission electron microscopy (TEM), a technique that allows the quantification of granule size, number, and subcellular distribution (20).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Using biochemical measurements of PG and MG in human skeletal muscle, we have shown that PG accumulation is the initial event during glycogen resynthesis (0 -4 h) followed by increases in MG (4 -24 h) (2). These data are consistent with the findings of Elsner et al (11), who have demonstrated using radiolabeled glucose a doubling of glycogen concentration in the early phases of glycogen resynthesis yet no increase in glycogen granule size in cultured rat myotubes. These findings have also been confirmed visually using transmission electron microscopy (TEM), a technique that allows the quantification of granule size, number, and subcellular distribution (20).…”
Section: Discussionsupporting
confidence: 82%
“…Given this, glycogen resynthesis likely involves 1) the synthesis of new GN-1 protein or 2) the addition of glucose residues to existing glycogen structures. Biochemical and electron microscopic data show both mechanisms to be involved, as there is an increase in granule size and number with glycogen resynthesis (11,21). New glycogen granule formation would theoretically require the synthesis of new GN-1 protein.…”
mentioning
confidence: 98%
“…Primary skeletal muscle cell culture Primary cultures of myotubes were prepared from the hindleg muscles of 21-day-old Wistar rat foetuses by a modification of the methods described by Elsner et al [20].…”
Section: Methodsmentioning
confidence: 99%
“…The initial phase of recovery is characterized primarily by an increase in PG followed by an increase in MG; this may reflect an initial increase in the number of small granules, followed by their enlargement and development into larger, mature granules (2, 28). Elsner et al (10) demonstrated an "ordered" pattern of granule synthesis using cultured rodent myotubes, in that existing granules appear to accept CHO initially, but the cell quickly begins to generate new granules even though the existing ones were only intermediate in size. However, it needs to be noted that the glycogen stores of the myotubes were only moderately compromised prior to the synthesis period.…”
Section: Discussionmentioning
confidence: 99%
“…Work with cultured myotubes (10) suggests that some glycogen granules may be completely catabolized when glycogen stores are decreased. Under these circumstances, it is unknown whether the protein is degraded or is liberated as apoprotein (apo)-GN-1 (i.e., unglucosylated) and/or is translocated.…”
mentioning
confidence: 99%